The design of a hard rock permittivity and loss sensor to be integrated with borehole radar - Kotze, Beukes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2004.